Effect of Mixed Probiotics on Alleviating H1N1 Influenza Infection and Regulating Gut Microbiota - Hongchao Wang; Yuhao Zhao; Zhangming Pei; Jianxin Zhao; Pinghu Zhang; Xinyue Zhang; Zhijian Zhang; Wenwei Lu (Foods)
Influenza and other respiratory infections cause annual epidemics worldwide, with high incidence and mortality rates reported among immunocompromised infants and elderly individuals. Probiotics can modulate the immune system through their bacterial compositions and metabolites, affecting influenza infections and effectively responding to viral mutations. Therefore, we evaluated the anti-influenza effects of mixed probiotics administered orally before and after influenza infection. The results showed that the mixed probiotics consisting of Lacticaseibacillus rhamnosus CCFM1279, Limosilactobacillus reuteri CCFM1145, and Lacticaseibacillus casei CCFM1127 inhibited viral replication and reduced lung inflammatory damage against influenza. In addition, the mixed-probiotics treatment activated the systemic immune response of the host. The gut microbiota analysis revealed a notable increase in the abundance of Alistipes and Rikenella following mixed-probiotic supplementation. The metabolomic analysis indicated a significant increase in adenosine levels, which was positively correlated with the abundance of Parvibacter. These findings highlight the effectiveness of mixed probiotics in fighting influenza viruses and suggest that certain gut microbiota and their metabolites may play a significant role in influencing the outcomes of influenza infections.